PERTUMBUHAN TANAMAN SELADA AKUAPONIK DENGAN MEDIA TANAM YANG BERBEDA - Marlendi, Sri; Rindawati; Rahman, Arief; Suparno (Agrienvi: Jurnal Ilmu Pertanian, 2023)
This study aims to determine the effect of aquaponics on the growth and yield of lettuce plants with different planting media. This research was conducted at the Samarinda State Agricultural Polytechnic from July to September 2023. The research was conducted using a completely randomised design with the treatment of planting media consisting of three levels, namely: P1 = Coconut fibre, P2 = Ironwood powder, and P3 = Coconut fibre and Ironwood powder, and each was repeated 3 (three) times. The parameters observed included water pH, water concentration, water temperature, plant height, number of leaves, leaf area, wet weight, and dry weight of lettuce plants. The data obtained were analysed by F-test analysis with a significance level of 5%. If the treatment affects the variables observed, it is continued with the 5% BNJ test. The results showed that the coconut fibre planting media treatment was the best treatment with a plant height of 55.50 mm, number of leaves 3.33 leaflets, leaf area index 1724.67 mm2, wet weight 0.60 grams, and dry weight 0,140 grams.